Impaired sleep and recovery after night matches in elite football players. Issue 14 (17th July 2016) - Fullagar, Hugh H. K.; Skorski, Sabrina; Duffield, Rob; Julian, Ross; Bartlett, Jon; Meyer, Tim
ABSTRACT: Despite the perceived importance of sleep for elite footballers, descriptions of the duration and quality of sleep, especially following match play, are limited. Moreover, recovery responses following sleep loss remain unclear. Accordingly, the present study examined the subjective sleep and recovery responses of elite footballers across training days (TD) and both day and night matches (DM and NM). Sixteen top division European players from three clubs completed a subjective online questionnaire twice a day for 21 days during the season. Subjective recall of sleep variables (duration, onset latency, time of wake/sleep, wake episode duration), a range of perceptual variables related to recovery, mood, performance and internal training loads and non-exercise stressors were collected. Players reported significantly reduced sleep durations for NM compared to DM (−157 min) and TD (−181 min). In addition, sleep restfulness (SR; arbitrary scale 1 = very restful, 5 = not at all restful) and perceived recovery (PR; acute recovery and stress scale 0 = not recovered at all, 6 = fully recovered) were significantly poorer following NM than both TD (SR: +2.0, PR: −2.6), and DM (SR: +1.5; PR: −1.5). These results suggest that reduced sleep quantity and quality and reduced PR are mainly evident following NM in elite players.